2011
DOI: 10.1007/s10870-011-0251-z
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Crystal Structure of Betulin–DMSO Solvate

Abstract: Betulin is a lupane triterpenoid [lup-20(29)-ene3b,28-diol, C 30 H 50 O 2 ] showing high biological activity. This activity is supposed to be strongly affected by the molecular structure of its polymorphic forms. Different solvate polymorphic forms of betulin have aroused increasing interest as the possible anticancer agents of natural origin. X-ray diffraction was used to investigate crystal structure of (1:1) betulin-DMSO solvate. Title compound crystallizes in the orthorhombic P2 1 2 1 2 1 space group. Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
5
23
0
Order By: Relevance
“…Such ring conformation is similar to that found in solvates of betulin [27], betulinic acid [28], and 28-O-propynoylbetulin [2].…”
Section: Crystal Structure Of 29-diethoxyphosphoryl-28-cyclopropylprosupporting
confidence: 80%
“…Such ring conformation is similar to that found in solvates of betulin [27], betulinic acid [28], and 28-O-propynoylbetulin [2].…”
Section: Crystal Structure Of 29-diethoxyphosphoryl-28-cyclopropylprosupporting
confidence: 80%
“…Recent results presented by Drebushchak et al18 showed that the similar twist of the isopropenyl group was observed for the betulin–ethanol solvate, where the torsion angle C29–C20–C19–C21 was 88.64°. For betulin–DMSO solvate, the corresponding torsion angle was equal to −96.84° according to the results of Boryczka et al19 All quoted results suggest that the orientation of the isopropenyl group can be influenced by the kind of solvent used; however, this supposition needs more experimental work, especially in view of very limited amount of solvent used. The kind of solvent used for preparing the crystal and the role of H‐bonding in formation of different orientations of the isopropenyl group will be a subject of future work.…”
Section: Resultsmentioning
confidence: 60%
“…Different conformations of ring A are presented in Figure 4. The chair conformation of ring A was also observed for betulin–ethanol solvate,18 betulin–DMSO solvate,19 betulinic acid–benzyl ester,13 and 3β‐O‐feruloylbetulinic acid 14. All these compounds possess at the position C3 the hydroxyl group instead of the carbonyl group, which is present in BA.…”
Section: Resultsmentioning
confidence: 75%
“…All other protons were distributed among numerous peaks located between 0.63 ppm and 2.00 ppm. Boryczka et al (2012) reported similar NMR analyses for betulin.…”
Section: Nmr Analysismentioning
confidence: 62%